Assessing quality of life in people with multiple sclerosis - Nicholl, C R; Lincoln, N B; Francis, V M; Stephan, T F (Disability and rehabilitation, 2001)
Purpose : The quality of life of multiple sclerosis (MS) patients was assessed using two MS specific quality of life measures (FAMS and SF-54) and a short generic measure (EuroQol) in order to make recommendations for routine assessment. Factors contributing to quality of life within this population were also considered. Method : Questionnaires were either sent by post or completed at interview. Ninety-six MS patients known to a consultant in rehabilitation medicine completed the questionnaires. Results : Patients scored very low on subscales related to physical health. Correlations were high between the FAMS and SF-54 but low with the EuroQoL. Stepwise multiple linear regressions showed mood measures to account for the most variance on all quality of life composite scores. The MS patients within the study had much lower SF-36 quality of life scores than the general population and other illness groups. Conclusions : The EuroQol did not measure the same aspects of quality of life as the FAMS and SF-54 and was not found to be a sensitive measure within this sample. The SF-54 suffered from floor effects on physical health subscales and therefore the FAMS was recommended.